2016
DOI: 10.17665/1676-4285.20165296
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de intervenção educativa sobre eventos adversos pós-vacina pentavalente: estudo quase-experimental

Abstract: Aim:  To  evaluate  the  knowledge  of  mothers  regarding  adverse consequences from the pentavalent vaccination before and after they participated in an educative  intervention.  Method:  This is  a  quasi-experimental  study,  with  a  before-and-after analysis, of a single group of 100 mothers of breastfeeding babies, from September to October 2014, in an outpatient clinic of a public maternity hospital in the municipality of  Imperatriz,  Brazil.  Results:  Following  the  intervention, a  significant  in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In this research, among the items that showed improvement of maternal knowledge, we highlight the stimulation of affective interaction, because mothers recognize the importance of love, affection and attention to the child as decisive aspects for a successful development. This reinforces the idea that affectivity is considered one of the fundamental care practices for the child, and the family should be stimulated in this regard, so that it can transform the reality in which the child lives ( 24 ) .…”
Section: Discussionsupporting
confidence: 72%
“…In this research, among the items that showed improvement of maternal knowledge, we highlight the stimulation of affective interaction, because mothers recognize the importance of love, affection and attention to the child as decisive aspects for a successful development. This reinforces the idea that affectivity is considered one of the fundamental care practices for the child, and the family should be stimulated in this regard, so that it can transform the reality in which the child lives ( 24 ) .…”
Section: Discussionsupporting
confidence: 72%